2008
DOI: 10.1371/journal.pone.0003482
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Impairs the Function of Plasmacytoid Dendritic Cells in Lymphoid Organs

Abstract: Human dendritic cells (DCs) are the main antigen presenting cells (APC) and can be divided into two main populations, myeloid and plasmacytoid DCs (pDCs), the latter being the main producers of Type I Interferon. The vast majority of pDCs can be found in lymphoid organs, where the main pool of all immune cells is located, but a minority of pDCs also circulate in peripheral blood. Human cytomegalovirus (HCMV) employs multiple mechanisms to evade the immune system. In this study, we could show that pDCs obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 54 publications
1
24
2
Order By: Relevance
“…Indeed, the contribution of viruses (e.g., herpesviruses) to the development of MS (33,34) and modulation of pDC subpopulations in blood and tissue under human CMV (HCMV) infection (35) have been described. Thus, the expression of cell surface markers on pDCs was shown to be differently regulated in response to HCMV infection (35). These results imply that, similar to HCMV infection, a yet unidentified low-virus infection persistency in patients with MS could selectively target pDC population in the blood, changing their phenotype and function.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, the contribution of viruses (e.g., herpesviruses) to the development of MS (33,34) and modulation of pDC subpopulations in blood and tissue under human CMV (HCMV) infection (35) have been described. Thus, the expression of cell surface markers on pDCs was shown to be differently regulated in response to HCMV infection (35). These results imply that, similar to HCMV infection, a yet unidentified low-virus infection persistency in patients with MS could selectively target pDC population in the blood, changing their phenotype and function.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, our study demonstrated that the decrease in pDC with age previously reported is associated with CMV seropositivity and that CMV seropositivity which is known to influence T lymphocyte subsets also influenced DC of lymphoid origin. This result could appear paradoxical because it was shown that nonclassical monocytes and mDC are infected by CMV while pDC are not, although some conflicting results were obtained in humans from in vitro studies . However, pDC play a key role in the innate response against CMV by producing interferon type I.…”
Section: Discussionmentioning
confidence: 99%
“… 84 pDCs isolated from peripheral blood or lymphoid organs (tonsils) consist of two subpopulations that behave differently upon HCMV infection: blood-pDCs (bpDCs), which are resistant to HCMV infection, and tonsillary pDCs (tpDCs), which are fully permissive 85 . In tpDCs, HCMV infection reduces expression of adhesion and costimulatory molecules and the ability to allogeneically stimulate T cells and impairs IFN-α production 85 . In bpDCs, infection leads to activation, increases expression of MHC class I, adhesion molecules and costimulatory molecules and production of IFN-α, 85 but markedly reduces allogeneic T-cell stimulation.…”
Section: Hcmv Infection In Plasmacytoid Dcsmentioning
confidence: 99%
“…In tpDCs, HCMV infection reduces expression of adhesion and costimulatory molecules and the ability to allogeneically stimulate T cells and impairs IFN-α production 85 . In bpDCs, infection leads to activation, increases expression of MHC class I, adhesion molecules and costimulatory molecules and production of IFN-α, 85 but markedly reduces allogeneic T-cell stimulation. The decrease in allogeneic T-cell stimulation in infected tpDCs and bpDCs was mediated by an HCMV-induced soluble factor.…”
Section: Hcmv Infection In Plasmacytoid Dcsmentioning
confidence: 99%